Surrogacy and the Motherhood Question in Yoruba Culture - Oluwaseyi, Oyekan Adeolu; Esther, Ani Amara (Bangladesh Journal of Bioethics, 2017)
One of the arguments against surrogacy is that it is harmful to both the surrogate mother and the child. Numerous strands of this argument are collectively referred to as the ‘harm factor’. A version of the argument says that surrogacy interrupts the Mother-fetal affection which develops between the surrogate mother and the child. If this is true, what implication does it have for the concept of motherhood? Does the biological connection between the fetus and the surrogate put the latter in a better position as a mother than the commissioning mother? This paper examines the relationship between surrogacy and motherhood within the context of Yoruba culture. It argues that the culture emphasizes the sociological dimension of motherhood more than the biological. This, the paper argues, is because of the culture’s emphasis on the significance of nurture and care to the development of a meaningful and stable life. The paper thus concludes that while Yoruba traditional society lacked the scientific wherewithal to undertake a successful surrogacy procedure, its conception of motherhood, prevalently held even in contemporary time, is normatively compatible with surrogacy.